The Brazilian beef meat sector into a domestic and international context: a Supply Chain Management (SCM) approach - Valdes, Rodrigo; Diaz Osorio, Jose (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2015)
The study of regional competitiveness of agricultural markets stresses the importance of market dynamics into a Supply Chain Management (SCM) framework. The aim of this paper was to carry out a descriptive analysis of the Brazilian beef meat sector focusing on the role of inter-firm collaboration as a source of value-added and competitive strength into the MERCOSUR context. It was applied two conceptual frameworks. The first one developed by Lambert and Cooper (2000) focus on an integration of the SCM and the second, proposed by Obersojer and Weindlmaier (2008) focus on an Efficient Consumer Response (ECR). From the first approach, it was identified structural problems that limit the integration of the SCM process of this sector, mainly due to difficulties to implement quality and safety standards due to its regional diversification. From the second, we concluded that distrust in the relationship between processing companies and retailers and a lack of strategic consumer orientation were the main obstacles for subsequent implementation of an ECR framework in the beef meat sector. Finally, it is desirable a management structure that enforces the capability of the different areas to increase the coordinating level among its respective chains.